Prenatal alcohol prevention in the UK: mapping the landscape through systematic collaborative review. (November 2022) - McQuire, Cheryl; Zuccolo, Luisa; Frennesson, Felicia; Butcher, Sandra; Carel, Havi; Cook, Penny; Dvorak, Tadeas; Gilham, Ellie; Hurt, Lisa; Langford, Rebecca; Misell, Andrew; Mukherjee, Raja; et al.
Abstract: Background: UK policy makers have called for urgent action to reduce prenatal alcohol exposure (PAE), but evidence on what is effective is scarce. We aimed to identify, evaluate, and synthesise evidence on content, process aspects, and effectiveness of UK PAE prevention initiatives. Methods: We conducted a systematic search of published and grey literature on UK PAE prevention (PROSPERO: CRD42020209460); consultations with 61 academic, practice, policy, third sector, and public stakeholders; and semi-structured 12 interviews with pregnant people (who were aged ≥18 years and ≥12 weeks' gestation) and service providers to discuss experiences of PAE prevention. Participants were purposively sampled to cover each UK region and identified through maternity sites, social media and, for stakeholder consultees, researcher networks. Information from relevant PAE prevention initiatives from the literature was independently extracted by two reviewers. Ethical approval and informed consent were obtained for interviews, which were recorded and transcribed. Qualitative evidence was synthesised using thematic analysis. Quantitative data will be summarised using descriptive statistics and meta-analysis. Findings: We identified 14 PAE prevention initiatives through literature searches (22 of 4064 results were eligible), stakeholder consultation, and interviews. Initiatives included screening and intervention, campaigns, and education or training. Seven initiatives were identified in the north of England. Two initiatives were identified in Scotland and two in Wales. The East of England, West Midlands, and South East of England had one each. None were identified in Southwest of England or Northern Ireland. Barriers to prevention included absence of resources, excessive workload, concerns around blame, and COVID-19. Enablers included workforce training and trust between pregnant people and service providers. Effectiveness of evidence was scarce. Interpretation: Key strengths include extensive searches and multidisciplinary consultation. Data collection and analyses are ongoing and will be finalised before November, 2022. This research will provide a comprehensive analysis of current provision, providing crucial evidence to inform research and practice. Funding: The National Institute for Health and Care Research.